BREATHLESS IN SINDH: THE HIDDEN THREAT OF BIRD-BORNE RESPIRATORY DISEASES IN URBAN AREAS(A CROSS-SECTIONAL STUDY FOR PUBLIC HEALTH CONCERN USING ONE HEALTH APPROACH) (Journal of Medical & Health Sciences Review, 2025)
Background: Rapid urbanization in Sindh, Pakistan, especially in cities like Karachi, Hyderabad, and Sukkur, fosters close human interactions with urban birds such as pigeons, sparrows, and mynahs. These birds serve as reservoirs for zoonotic pathogens (e.g., Chlamydia psittaci, Salmonella spp., Cryptococcus neoformans) which can cause respiratory infections in humans. Environmental factors like pollution and poor waste management exacerbate exposure risks by impairing lung defenses and facilitating pathogen transmission.Objectives: To assess the association between urban bird exposure and respiratory health outcomes among adults aged 25-45 years in Sindh’s major cities, incorporating environmental pollution and other confounders.Methods: A six-month cross-sectional analytical epidemiological study (March to August 2024) was conducted on a stratified random sample of 600 adults (200 each from Karachi, Hyderabad, and Sukkur), stratified by bird exposure levels. Data combined human surveys, biological sampling (avian droppings and blood), and environmental sampling (soil, water, PM2.5 levels). Pathogen detection used PCR and culture methods. Respiratory symptoms and risk factors were analyzed via descriptive statistics, chi-square tests, and logistic regression models. Results:• Prevalence of zoonotic pathogens in urban birds: Chlamydia psittaci (18%), Salmonella spp. (12%), Cryptococcus neoformans (8%), highest in Karachi.• Respiratory symptom prevalence was significantly higher in individuals with high bird exposure (43.3%) compared to low exposure (23%).• Logistic regression showed high bird exposure increased odds of respiratory symptoms by 2.53 times (95% CI: 1.80–3.56, p < 0.001), even after adjusting for PM2.5 pollution, smoking status, occupation, age, and gender. PM2.5 pollution and smoking also significantly increased respiratory risk. Age and gender were not significant predictors.Conclusions: Urban birds in Sindh harbor significant zoonotic respiratory pathogens, and high exposure is strongly linked with increased respiratory symptoms among urban adults. This risk is compounded by environmental pollution and smoking. The study underscores the urgent need for integrated One Health interventions including surveillance, public education, urban wildlife management, and pollution control to mitigate zoonotic respiratory disease burden in rapidly urbanizing South Asian cities.